Micro Organic Light Emitting Diode Arrays by Patterned Growth on Structured Polypyrrole. Issue 10 (9th March 2020) - Li, Jianping; Hu, Yun; Liang, Xianhu; Chen, Jianmei; Zhong, Liubiao; Liao, Liangsheng; Jiang, Lin; Fuchs, Harald; Wang, Wenchong; Wang, Yandong; Chi, Lifeng
Abstract: Patterning organic light emitting diodes (OLEDs) with several micrometers resolution is of importance in applications such as micro displays, virtual and augmented reality devices. Here a fabrication method of micro OLEDs is reported, using conducting polymer polypyrrole (PPy) as nucleation layer. The photolithographically patterned PPy films are used for patterned growth of hole transport layer to locally confine carrier injection. High‐resolution red, green, and blue micro OLED arrays are demonstrated. The green micro OLEDs with stacked structure of Al/Alq3 /NPB/PPy/ITO exhibit a maximum current efficiency of 3.41 cd A −1, which is 80% in comparison to those devices on indium tin oxide glass. Abstract : Using photolithographically patterned polypyrrole films, the fabrication of micro organic light emitting diode arrays is developed by patterned growth of the hole transport layer. The devices exhibit a maximum current efficiency of 3.41 cd A −1, which is 80% in comparison to those devices on indium tin oxide glass.